Deciphering the mechanism of Fang-Ji-Di-Huang-Decoction in ameliorating psoriasis-like skin inflammation via the inhibition of IL-23/Th17 cell axis. (5th December 2021) - Song, Chenglin; Yang, Chenxi; Meng, Siwei; Li, Manru; Wang, Xiao; Zhu, Yaoxuan; Kong, Lingdong; Lv, Wen; Qiao, Hongzhi; Sun, Yang
Abstract: Ethnopharmacological relevance: In the theory of traditional Chinese medicine (TCM), the etiology of psoriasis is assigned to damp-heat internal depression, blood poisoning, Yin deficiency and loss of nourishment. Fang-Ji-Di-Huang-Decoction (FJDH), a well-known Chinese traditional formula, is recorded in Synopsis of the Golden Chamber (in the Eastern Han Dynasty). This decoction is composed of dried roots of Rehmannia glutinosa (Gaertn.) DC., dried roots of Stephania tetrandra S. Moore, roots of Saposhnikovia divaricata (Turcz.) Schischk., dried twigs of Cinnamomum cassia (L.) J. Presl and dry roots and rhizomes of Glycyrrhiza uralensis Fisch. FJDH has the function of clearing heat, removing dampness, and nourishing blood. Therefore, in modern medical theory, FJDH can regulate the infiltration of inflammatory cells and the secretion of inflammatory cytokines in the process of psoriasis. Aim of the study: This study evaluated whether FJDH treated psoriasis and its specific mechanism for the efficacy in mice. At the same time, it clarified s what important role of the copperware played s in the curative effect of FJDH. Methods and materials: We used imiquimod (IMQ) to induce psoriasis-like skin inflammation in mice. Mice were treated with imiquimod for one week, and FJDH was given by intragastric administration one week in advance. Record the weight change and psoriasis Area and Severity Index (PASI) score of the mouse during the whole process to assess the severity of psoriasis were recored mouse. Hematoxylin-eosin staining was used to evaluate skin tissue structure change. Immunohistochemistry was performed to observe the expressions of Ki67 and proliferating cell nuclear antigen (PCNA) in skin tissue. In order to further explore the mechanism of FJDH in the treatment of psoriasis, we used network pharmacology to predict the therapeutic target. TCMSP and Uniprot were used to collect compounds and genes of FJDH. Genecards was used for obtaining genes of psoriasis. String was used to analyze the relationship between genes. Metascape was used for gene enrichment and pathway prediction. Using molecular biological detection methods, we verified whether FJDH could regulate Interleukin 17 signaling pathway and T helper cell 17 (Th17) cell differentiation. Flow cytometry was used to detect Th17 cell differentiation in mouse spleen. Quantitative Real-time PCR was used to detect mRNA expression of IL-17 signaling pathway-related inflammatory factors in mouse skin tissues. UPLC-Triple TOF-MS/MS and Phenol-Sulphate colorimetry were used to explore the main components of FJDH, and further elaborate the mechanism of FJDH in the treatment of psoriasis. Results: FJDH with copper was found to improve psoriasis-related pathological symptoms in a dose-dependent manner, possibly by inhibiting IL-23/Th17 cell axis and reducing inflammatory cytokines such as IL-17A, IL-17F, IL-22 and TNF-α. Furthermore, R. glutinosa polysaccharide in FJDH was the main substance that exerted the drug effect and it work by forming a complex with copper. Experimental data proved that Rehmannia glutinosa polysaccharide and copper complex had the same pharmacological activity and therapeutic effect as FJDH. Conclusions: FJDH may attenulated imiquimod-induced psoriasis-like skin inflammation in mice by inhibiting IL-23/Th17 cell axis. The material basis for the therapeutic effect may be the formation of complexes between the polysaccharides of R. glutinosa and copper in FJDH to produce the effect. These findings suggest that FJDH can be used as an effective Chinese medicine to treat psoriasis. Graphical abstract: Image 1